Impact of self-esteem and overall life satisfaction on perceived social competence in university students - Kamran, Muhammad; Saab, Marwa; Niaz, Urooj; Aslam, Sarfraz; Amjad, Amjad Islam (Institute of Advanced Engineering and Science, 2025)
Positive psychology is transformative in developing individuals’ self-esteem, life satisfaction, subjective happiness, and social competence. The objectives of the present study were to investigate the impact of self-esteem and overall life satisfaction on perceived social competence in university students while measuring subjective happiness as a mediator and gender differences across variables. A sample of 1,168 participants was selected using purposive and random sampling techniques across universities in Pakistan. The study design was correlational with a quantitative method. Four scales, the Rosenberg self-esteem scale (RSE), satisfaction with life scale (SWLS), subjective happiness scale (SHS), and perceived social competence scale (PSCS), were administered to measure the variables. Pearson correlation and mediation models were used to test the hypotheses. The analysis indicated that subjective happiness mediated the relationship between self-esteem, perceived social competence, life satisfaction, and perceived social competence. Moreover, the results showed that males scored higher than females in terms of levels of self-esteem. No significant gender difference existed in life satisfaction, subjective happiness, and perceived social competence. These findings may significantly enrich the literature on positive psychology in Pakistani university students and can assist universities in their mental health programs and sustain students’ healthier well-being.